Analysis of The Influence of Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Price Earning Ratio on Stock Returns with Return on Asset as A Moderation Variable - Dwi Susilo; Triana Ismawati (ProBisnis : Jurnal Manajemen, 2023)
This study aims to examine and analyze the effect of the Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Price Earning Ratio on Stock Returns with Return on Assets as a Moderating Variable. The object of this research is companies indexed LQ45 on the Indonesia Stock Exchange in 2019-2021. The sampling method used purposive sampling and obtained data for 135 companies. The analysis technique used is Multiple Regression Analysis and Moderated Regression Analysis (MRA) using SPSS version 20. The results show that the Current Ratio (CR) has a negative and insignificant effect on stock returns; Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) have a negative and significant effect on Stock Returns, while the Price Earning Ratio (PER) has a positive and significant effect on Stock Returns.